Acute hydrothorax from peritoneal dialysis successfully treated with new dialysis regime - Lim, Christopher Thiam Seong; Thong, Kah Mean (Pakistan Medical Association Rawalpindi Islamabad Branch, 2015)
Hydrothorax is a rare and often unrecognized complication associated with peritoneal dialysis (PD). This is usually due to the presence of pleuroperitoneal fistula. Most nephrologist will choose to cease the peritoneal dialysis and rest the peritoneum. More than often surgical interventions include pleurodesis or thoracotomy will be required. In this report, we reported a patient who developed pleural effusion after starting continuous ambulatory peritoneal dialysis. She was successfully managed by the use of low volume exchange during daytime with avoidance of conversion to haemodialysis or any surgical intervention.